Defects of leukocyte migration in primary immunodeficiencies. Issue 6 (21st June 2013) - Badolato, Raffaele
<x xml:space="preserve">Abstract</x> This Viewpoint gives an overview of the inherited disorders that are characterized by defects of leukocyte trafficking. Three paradigmatic diseases have been selected: warts, hypogammaglobulinemia, infections, and myelokathexis; Wiskott–Aldrich; and leukocyte adhesion deficiency syndromes. These conditions encompass defects in the steps that are required for leukocyte motility: from the response to chemokines, which is altered in warts, hypogammaglobulinemia, infections, and myelokathexis syndrome, to the impairment of leukocyte adhesion and migration found in leukocyte adhesion deficiency syndrome, and finally to abnormal actin filament formation, which is affected in leukocytes of Wiskott–Aldrich syndrome patients.